Feeding resources and management among poor livestock keeper : A field study in linkage villages - Singh, B.P.; Sharma, M.C.; Tiwari, R. (2009)
The livestock keepers fed their livestock according to their socio-economic and socio-cultural status. Largely their livestock fed on crop residues like grasses, wheat and paddy straw, sugarcane top and left-over feed of other animals and rarely adopt recommended feeding technologies, because of non-availability, high cost and ignorance. The feeding of paddy straw was mainly prevalent in study area which needs physical, chemical or biological treatment to enrich its quality and palatability. Extension education programme played a vital role in enhancing the knowledge level among livestock owners about improved livestock feeding.